REGULATORY AND LEGAL PROVISION OF ACCOUNTING AND CONTROL OF SETTLEMENTS WITH SUPPLIERS AND CONTRACTORS (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Annotation. The organization of accounting for accounts payable at any enterprise is quite important, because it contributes to the reliability, correctness and transparency of the display of data from settlement transactions with suppliers and contractors. The article discusses the peculiarities of accounting for payments with suppliers and contractors. The purpose of the article is to clarify the economic meaning of the terms "supplier", "contractor", "creditor debt" and to reveal their role in the country's economy. It was determined that accounts payable is the organization's debt to other legal entities and individuals, which appears as a result of a time gap between the provision of goods and materials, the receipt of goods and services, the provision of services, the receipt of a preliminary cash advance and the date of their actual payment and fulfillment of obligations to third parties. The current legal acts regulating the accounting of settlements with suppliers and contractors were analyzed; the theoretical aspects of their accounting and analytical support are systematized, as well as the documentation of transactions with these counterparties is displayed. Ways and directions for further improvement of accounts payable management are proposed. It was revealed that with the help of keeping analytical documentation, accounts payable will be improved, namely, control of the timeliness of payments with each supplier or contractor for the delivered values ​​will be improved, and as a result, this will have a positive impact on the company's financial condition. It was identified that the main methods of managing payables are: control over the ratio of payables; assessment of accounts payable; analysis of settlements with creditors, their registration.
Keywords: accounting, accounts payable, suppliers, contractors, obligations, settlements with suppliers and contractors, regulatory and legal support for settlements with suppliers and contractors